Children and youth with myelomeningocele's independence in managing clean intermittent catheterization in familiar settings - Donlau, M.; Imms, C.; Mattsson, G.; Mattsson, S.; Sjors, A.; Falkmer, Torbjorn (Wiley-Blackwell, 2010)
Aim: To examine the ability of children and youth with myelomeningocele to independently manage clean intermittent catheterization. Methods: There were 50 participants with myelomeningocele (5–18 years); 13 of them had also participated in a previous hospital-based study. Their abilities and interest in completing the toilet activity were examined at home or in school using an interview and the Canadian Occupational Performance Measure (COPM). Actual performance was observed and rated. Background variables were collected from medical records and KatAD+E tests.Results: In total, 48% were observed to perform the toilet activity independently, in comparison with 74% who self-reported independence. Univariate analyses found KatAD+E could predict who was independent. COPM failed to do so. Ability to remain focused and ambulation were predictors of independence, but age, sex and IQ were not. Multivariable analysis found time to completion to be the strongest predictor of independence. Four children were independent in their familiar environment, but not in the hospital setting, and six of 13 children maintained focus only in their familiar environment. Conclusions: Interviews were not sufficiently accurate to assess independence in the toilet activity. Instead, observations including time to completion are recommended. The execution of the toilet activity is influenced by the environmental context.